2023
DOI: 10.3390/nu15081840
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Programming of the Lifespan of Male Drosophila by Activating FOXO on Larval Low-Nutrient Diet

Abstract: Nutrition during the developmental stages has long-term effects on adult physiology, disease and lifespan, and is termed nutritional programming. However, the underlying molecular mechanisms of nutritional programming are not yet well understood. In this study, we showed that developmental diets could regulate the lifespan of adult Drosophila in a way that interacts with various adult diets during development and adulthood. Importantly, we demonstrated that a developmental low-yeast diet (0.2SY) extended both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…FOXO proteins regulate cell cycle arrest and apoptosis, but also play a crucial role in differentiation [127]. FOXO homologues in C. elegans and the silkworm are active in lifespan extension [128,129]. In humans, FOXO3 is responsible for longevity [130].…”
Section: Foxomentioning
confidence: 99%
“…FOXO proteins regulate cell cycle arrest and apoptosis, but also play a crucial role in differentiation [127]. FOXO homologues in C. elegans and the silkworm are active in lifespan extension [128,129]. In humans, FOXO3 is responsible for longevity [130].…”
Section: Foxomentioning
confidence: 99%
“…Lastly, a study by Gao et al [3] described the effect of developmental diets (a low-yeast diet) on regulating the lifespan of adult Drosophila during development and adulthood. It was demonstrated that a developmental diet achieved the nutritional programming of the lifespan of adult males by modulating the activity of dFOXO in Drosophila.…”
mentioning
confidence: 99%